THEORETICAL FOUNDATIONS FOR IMPROVING THE EFFICIENCY OF AUTOMATIC LOAD SHEDDING IN A POWER SYSTEM - YASAK, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study examines theoretical aspects of improving the efficiency of automatic load shedding in power systems. This utilizes specific parameters for setting up the relevant equipment for operation. Criteria for automatic load shedding of the network and a sequence of future actions for experimental research on the topic have been formed. Among the criteria highlighted are the use of industrial controllers with different types of interfaces to reduce emergency response time, and the use of power quality assessment tools. A simulation model of Automatic Load Shedding (ALS) for a power system using the Python programming language is presented. The model accounts for the power balance between generation and load, where the frequency change is described by the equation ΔF = k·(P_gen - P_load) + ξ. The system includes 20 randomly distributed consumers (5–15 MW) and 4 ALS stages with thresholds of 49.5, 49.0, 48.5, and 48.0 Hz. The results demonstrate that during a power deficit (-0.6 Hz/sec), the frequency drops to 49.4 Hz, but after sequentially disconnecting 30% of the load, it stabilizes at the nominal level (50 Hz). Visualization confirms the effectiveness of multi-stage ALS, although the model does not account for generator inertia and network effects. The research underscores the importance of ALS for preventing accidents in power systems. A nonlinear relationship between the number of ALS stages and the stabilization time was identified, opening prospects for optimizing protection parameters. The obtained results can be used for predicting emergency scenarios under variable load conditions. The proposed toolkit is recommended for use as an additional element for supporting the country’s energy security. It complements and expands the capabilities of existing solutions.